Zoneamento da Reserva Particular do Patrimônio Natural Trápaga - Scarascia, Pietro de Oliveira (Universidade Federal de São Carlos, 2018)
In the last decades, the pressures and threats to the conservation of the Brazilian biodiversity have been increasing day by day. One of the strategies for the protection of natural heritage and biodiversity is the creation and implementation of Protected Areas (PA), which in Brazil are known as Conservation Units, and one of the categories of protected areas is the PNHR (Private Natural Heritage Reserve). The National System of Conservation Units recommends that all PAs should have a Management Plan, which should include a " zoning of the area " and the rules that should govern it. This study was carried out at the PNHR Trápaga, a private reserve of 70 ha, located in the municipality of São Miguel Arcanjo. The objective of this study was to elaborate the zoning of the PA using two different techniques, that is, the mapping of the soil use with remote sensing techniques, and the use of a Biotic Integrity Index (BII) applied to the vegetation of the same. In order to analyze the biotic integrity, the BII was used, which is composed of 11 ecological indicators (litter, clearings, exotic species, lianas, epiphytes, and late indicator species among others). For analysis of the BII, 20 plots of 10x10m randomly arranged in the area. The land use and cover mapping was based on an orbital image (resolution of 5 meters, from June 30, 2014), which was first classified by unsupervised method (K-means algorithm). Considering the result of the first, a supervised classification (Maximum Likelihood algorithm) was performed. The following management areas were used for the elaboration of the zoning thematic map: wild zone-WZ, protection zone-PZ, recovery zone-RZ and visitation zone-VZ. The results showed that 11 plots obtained BII-"Regular", seven-"Good", and only two-"Low". The results obtained BII showed moderate positive correlation (r = 0.03 p = 0.466) with NDVI values obtained in each plot. For the supervised analysis, seven polygons of plots with BII-"Good" and seven of plots with IIB-"Regular" were used. The Confusion Matrix of the supervised classification map elucidated an overall hit of 93.43%. The Confusion Matrix among the classification maps elucidated an overall hit of 90%. From the reliability of the BII correlation with the NDVI, and of the overall accuracy of the classification maps, the zones within the obtained classes were distributed. From this analysis the zoning of the area was elaborated, thus, class 1, represented by BII-“Good" was mapped as WZ (intangible zone); class 2, represented by IIB-"Regular" was mapped as PZ (primitive); and class 3, represented by IIB-"Low", was mapped as RZ (recovery zone). For the definition of VZ (visiting zone) was used earlier work already performed in the study area. Finally, the % of area occupied by each zone was 9% VZ, 17% RZ, 27% WZ and 47% PZ. The zoning map are proposed to be incorporated into the AP Management Plan, aimed at the seal of the government of this management tool.
Zoning of the Private Reserve of Natural Heritage of Trápaga
Keywords: Gestão; planejamento territorial; conservação; Unidades de Conservação; Management; Territorial planning; Conservation; Protect Areas; Gestão ambiental; Environmental management; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES